2018
DOI: 10.5588/ijtld.17.0827
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted chest radiography reading for tuberculosis screening in people living with diabetes mellitus

Abstract: CAD4TB has potential as a triage tool for TB screening in PLWD, thereby significantly reducing the need for microbiological examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…Within the triage use-case studies, 6/8 (75%) used a microbiologic reference standard on all participants [18, 19, 22, 25, 67, 68]. Within the screening studies, 4/5 (80%) used a microbiologic reference [20, 24, 69, 70]. In two Clinical studies, the CADscore was used to select which participants underwent microbiologic testing, hence the software’s diagnostic accuracy could not be assessed [17, 69].…”
Section: Resultsmentioning
confidence: 99%
“…Within the triage use-case studies, 6/8 (75%) used a microbiologic reference standard on all participants [18, 19, 22, 25, 67, 68]. Within the screening studies, 4/5 (80%) used a microbiologic reference [20, 24, 69, 70]. In two Clinical studies, the CADscore was used to select which participants underwent microbiologic testing, hence the software’s diagnostic accuracy could not be assessed [17, 69].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested thresholds between 60 and 85. 13,20,21 Several reports suggested that CAD4TB's threshold needs to be adjusted to study aims, the number of available microbiological tests, and underlying TB prevalence. 16,18,19,21,22 There has been no recommendation of a triage threshold for community-based screening programmes.…”
Section: Discussionmentioning
confidence: 99%
“…One study at a diabetes-care centre in Indonesia retrospectively evaluated CAD4TB and suggested a decision threshold score of 65-70. 20 Data on its performance in population-based screening is limited. Another study applied CAD4TB retrospectively in a non-clinical population-based setting and suggested that a lower CAD4TB score threshold would be required for triaging.…”
Section: Introductionmentioning
confidence: 99%
“…However, in comparison with the CAD4TB evaluation conducted in Pakistan among individuals with an unknown diabetes status that reported sensitivities in the range 91.0-97.3%, our current study shows lower sensitivities (range 48.6-90.5%) for the corresponding CAD4TB cut-offs on the same version of CAD4TB software on the same version of CAD4TB software 5 . A recent study from Indonesia evaluating CAD4TB among PWD reported an AUC of 0.89 using against the reference standard of bacteriologically and clinically confirmed TB (7 bacteriologically confirmed TB cases and 2 clinically diagnosed) 12 .…”
Section: Discussionmentioning
confidence: 99%